Real Estate Markets and Lending: Does Local Growth Fuel Risk? - Maximilian Zurek (Journal of Financial Services Research, 2021)
Real estate price growth affects credit risk for several reasons: it provides input for economic forecasts as it's closely tied to economic growth; when used as collateral by banks, rising real estate prices may decrease both expected and actual losses; and banks may become less risk averse in lending practices in the presence of rising property prices. Therefore, we analyze these effects on loan portfolios' estimated and realized risks on a local level. Using data of 390 German savings banks, however, we find that real estate prices have little or no impact on~savings banks' credit portfolio risk or risk precautions.
Keywords: G21; G32; G11; R31; 330; Lending risk; Regional banks; Collateral; Real estate markets